A novel murine model of late-phase reaction of immediate hypersensitivity. Issue 2 (1997) - Facincone Facincone, S. S.; De Siqueira De Siqueira, A. L. Pereira A. L. Pereira; Jancar Jancar, S. S.; Russo Russo, M. M.; Barbuto Barbuto, J. A. Marzagão J. A. Marzagão; Mariano Mariano, M. M.
Abstract : We describe here a novel experimental model of late-phase reaction of immediate hypersensitivity developed in mice. It consists of introducing small fragments of heat-coagulated hen egg white into the subcutaneous tissue of mice. After 14 days, animals challenged with purified ovalbumin into the footpad presented an immediate swelling of the paw peaking at 30 min, followed by two peaks of swelling at 6 and 24 h. Histological examination of the paws showed a massive eosinophil infiltration (more than 800 cells/5 microscopic fields). This intense infiltration persisted for more than 14 days after the challenge. Furthermore, in mice immunized with coagulated egg white the delayed swelling of the paws and eosinophilic infiltration were significantly higher than in mice immunized with the classical protocol of ovalbumin in alumen adjuvant. Transfer of lymph node cells obtained from mice implanted with heat-coagulated hen egg white induced footpad swelling and eosinophil infiltration in response to ovalbumin. High levels of ovalbuminspecific IgG1 but not of IgE were detected in the serum of these animals. The advantages of this model for the experimental study of late-phase reaction per se and its relevance to the study of allergic diseases such as asthma are discussed.